Biomedical Engineering: Frontier Research and Converging Technologies - Jo, Hanjoong; Jun, Ho-Wook; Shin, Jennifer; Lee, SangHoon (Biosystems & Biorobotics,, 2016)
This book provides readers with an integrative overview of the latest research and developments in the broad field of biomedical engineering. Each of the chapters offers a timely review written by leading biomedical engineers and aims at showing how the convergence of scientific and engineering fields with medicine has created a new basis for practically solving problems concerning human health, wellbeing and disease. While some of the latest frontiers of biomedicine, such as neuroscience and regenerative medicine, are becoming increasingly dependent on new ideas and tools from other disciplines, the paradigm shift caused by technological innovations in the fields of information science, nanotechnology, and robotics is opening new opportunities in healthcare, besides dramatically changing the ways we actually practice science. At the same time, a new generation of engineers, fluent in many different scientific "languages," is creating entirely new fields of research that approach the "old" questions from a new and holistic angle. The book reports on the scientific revolutions in the field of biomedicine by describing the latest technologies and findings developed at the interface between science and engineering. It addresses students, fellows, and faculty and industry investigators searching for new challenges in the broad biomedical engineering fields.